English with Lucy YouTube Channel to Teach Students’ Speaking Skill - Mutiarani Mutiarani; Muhamad Sofian Hadi; Firliani Azka Dwinanda (TEKNOSASTIK, 2022)
The research aimed to analyze speaking skill through “English with Lucy” YouTube channel. The research was conduct in the class 11 of SMK Kesehatan Letris Indonesia 2. The method of the research was Quantitative with Pre-experimental study. Writer choose one class as Experimental class. The used purposive sampling technique by choosing 33 participant and conducted pre-test and post-test to gather the writer data. The experimental class was using “English with Lucy” YouTube channel on learning English. The writer lasted for four months and writer compared the results of pre-test and post-test through SPSS 22 to conclude the results of research. The experimental class results would be the conclusion of research as this class used Vlogger Video during the lesson. The highest score of the pre-test was 60. And the highest score of the post-test was 92. There were the differences between pre-test score and post-test score. The value of the df t-value is searched based on n=32 with a range of 0,025. Its df t-value is 25,14. Because the t-test value is higher than the df t-value (25.14 > 1.6956) h1 is accepted and h0 is rejected, so the learning method is successful in improving students’ speaking skill. It means that teaching speaking skill through “English with Lucy” YouTube channel was significant.